2000
DOI: 10.18388/abp.2000_3963
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and cytophysiological aspects of lanthanides action.

Abstract: Lanthanides, also called rare-earth elements, are an interesting group of 15 chemically active, mainly trivalent, f-electronic, silvery-white metals. In fact, lanthanides are not as rare as the name implies, except for promethium, a radioactive artificial element not found in nature. The mean concentrations of lanthanides in the earth's crust are comparable to those of life-important elements like iodine, cobalt and selenium. Many lanthanide compounds show particular magnetic, catalytic and optic properties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(83 citation statements)
references
References 35 publications
5
77
0
1
Order By: Relevance
“…For instance, europium as the representative of lanthanides has relatively long‐lived radioisotopes ( 152 Eu: t 1/2 ≈13.3 years; 154 Eu: t 1/2 ≈8.6 years) that may penetrate into human body and significantly alter normal physiological processes by inhibiting enzymes, regulating synaptic transmitters and blocking membrane receptors . Importantly, Eu 3+ is typically employed as the simulant for long‐lived radiotoxic actinides (An 3+ ) such as Am 3+ for their similar adsorption properties . However, the effective sequestration of actinides and lanthanides (Ln) from complex radioactive wastes, especially the high level liquid waste (HLLW) under strong acidic conditions, remains a serious challenge because of the effects of protonation and retardation of material stability .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, europium as the representative of lanthanides has relatively long‐lived radioisotopes ( 152 Eu: t 1/2 ≈13.3 years; 154 Eu: t 1/2 ≈8.6 years) that may penetrate into human body and significantly alter normal physiological processes by inhibiting enzymes, regulating synaptic transmitters and blocking membrane receptors . Importantly, Eu 3+ is typically employed as the simulant for long‐lived radiotoxic actinides (An 3+ ) such as Am 3+ for their similar adsorption properties . However, the effective sequestration of actinides and lanthanides (Ln) from complex radioactive wastes, especially the high level liquid waste (HLLW) under strong acidic conditions, remains a serious challenge because of the effects of protonation and retardation of material stability .…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: AChE; acetylocholinoesterase, AMPA; α-amino-3-hydroxy-5-methyl-4isoxazolepropionic acid glutamate receptor, Axud1; cysteine-serine-rich nuclear protein1, Adcy8; calcium-stimulated adenylyl cyclase, Cdd37; cell division 37 homologue, Fos; proto-oncogene AP-1 transcription factor subunit, G; protein G, GLAST; glutamateaspartate transporter GS; glutamine syntethase, KAR; kainate glutamatergic receptor, mGluR; metabotropic glutamate receptor, NERT; norepinephrine transporter, NMDA; N-methyl-D-aspartate glutamatergic receptor, PAG; phosphate activated glutaminase, Slc5a7; solute carrier family 5 member 7 gene, SNARE; soluble NSF attachment protein, TRPVs; vanilloid-type heat-activated ion channels,Ube2v1; ubiquitin-conjugating enzyme e2, VGKC; voltage-gated potassium channel, VGSC; voltage-gated sodium channels including lanthanides may modify channel gating or block ion currents (Elinder & Arhem, 2003). Because of its uniquely strong gating activity, La 3+ is sometimes called a "supercalcium" (Brown, Rathjen, Graham, & Tribe, 1990) and the effects of lanthanides on voltage-gated ion channels including potassium and calcium have been previously reported in diverse cell types (Pałasz & Czekaj, 2000). Trivalent lanthanide cations directly block ion flow through neuronal voltage-gated K + channels (VGKC) with a potency that varies inversely with the ionic radius (Alshuaib & Mathew, 2005;Enyeart, Gomora, & Enyeart, 1998).…”
Section: Anthanide S a S Modul Ator S Of Neuronal Ion Channel Phymentioning
confidence: 99%
“…[ 46 ] Further in vitro cellular studies suggested that RE 3+ ions may interfere with Ca 2+ channels owing to their comparable radius, thus affecting the physiological processes within the tissues. [ 47,48 ] Nevertheless, the rat studies suggested that Gd 3+ is less toxic than Mn 2+ , [ 49 ] although the latter is also a useful paramagnetic ion for constructing T 1 contrast agents. Until now, most clinical MRI contrast agents are chosen from Gd-chelates due to their low release levels of free Gd 3+ ions and quick renal clearance, although patients with renal disease are subjected to risks of severe complication such as nephrogenic systemic fi brosis.…”
Section: Gadolinium-based Npsmentioning
confidence: 99%